Incorporating the Winescape into the Theory of Planned Behaviour: Examining ‘New World’ Wineries - Quintal, Vanessa; Thomas, Ben; Phau, Ian (Pergamon, 2015)
The current study sets out to examine the winescape for its effects on wine tourist behaviour. In doing so, an empirical winescape scale is introduced to an established decision-making model, the theory of planned behaviour. A total of 1135 responses were collected through a survey that was self-administered to wine tourists across four wineries in Australia and the USA. Structural equation modelling suggested that winescape service staff and complementary product had significant effects on wine tourist attitude toward the winery, making them instrumental in wine tourist decision-making. Winescape setting and wine value were also significant attributes in influencing wine tourist attitude. Findings provide greater insight into which winescape attributes are most critical in shaping wine tourist attitude and in turn, behavioural intention toward the winery. The research model offers an empirical decision-making framework that is easy to use and generalisable in wine tourism contexts.